2013
DOI: 10.1136/bcr-2013-010294
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis verrucosa cutis in a patient with keloid over ear lobule

Abstract: SUMMARYTuberculosis (TB) is a global health problem with predominance in resource-poor countries. Extrapulmonary TB constitutes approximately 10% of the cases and can present as different forms depending on the route of entry. Cutaneous TB is a small subset of the extrapulmonary TB. Cutaneous TB can either be of primary origin or secondary origin or it can be a part of a systemic infection. TB verrucosa cutis (TBVC) is the exogenous reinfection of TB in a previously sensitised patient. Routine cultures do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Barring isolated case reports, 2,6–9 no case series exclusively describes CTB of the pinna. Unlike the Indian subcontinent where the lower half of the body is commonly affected with CTB, ear involvement is rare even in the western literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barring isolated case reports, 2,6–9 no case series exclusively describes CTB of the pinna. Unlike the Indian subcontinent where the lower half of the body is commonly affected with CTB, ear involvement is rare even in the western literature.…”
Section: Discussionmentioning
confidence: 99%
“…The other two common forms, tuberculosis verrucosa cutis and scrofuloderma, are distinctly rare on the pinna, and no such case was reported among our series. A recent report that describes CTB in a patient with keloid over the ear lobule looks more like a nodular lesion of LV, mistaken for tuberculosis verrucosa cutis 9 …”
Section: Discussionmentioning
confidence: 99%
“…pyrazinamide 25 mg/kg/day and nine months respectively. 4 Study by Padmavathy L et al managed TBVC of foot with miliary TB using isoniazid, rifampicin, pyrazinamide, ethambutol and corticosteroids. 11 Study by Mathur M et al showed the epidemiological, clinical and histological pattern of CTB in Nepal with LV, the most common clinical type (64%), followed by TBVC (19%).…”
Section: 13mentioning
confidence: 99%
“…1 Despite the high prevalence of TB, the extra-pulmonary form of TB, cutaneous tuberculosis (CTB) occurs rarely and includes only 1-2%. 3,4 Nevertheless, TB-prevalent developing countries reported a significant number of new cases of CTB, for instance, 18,000 in India, 580 in Peru in the year 1999. 5 CTB continues to be diagnostically elusive and is categorized based on inoculation mechanism, bacterial load on skin, immune hypersensitivity reactions to M tuberculosis antigens etc.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis verrucosa cutis is an exogenous infection occurring in a previously sensitized patient by direct inoculation of the organism. It occurs in sensitized patients with a moderate to high immune response [2] . We present a case of 23-year-old male patient with tuberculosis verrucous cutis on the foot.…”
Section: Introductionmentioning
confidence: 99%